The Relationship Between Maternal Knowledge and Family Support with Exclusive Breastfeeding in Tataaran II Village - Zefanya Claister Supit; Nancy S. Bawiling; Tika Bela Sari (Universitas Muhammadiyah Palu, 2026)
This study aims to determine the relationship between maternal knowledge and family support with exclusive breastfeeding for infants under 6 months in Tataaran II Village. The type of research used is a quantitative method with a cross-sectional study approach. The population in this study were all mothers who have infants aged 0–11 months in the working area of the Integrated Health Service Post (Posyandu) in Tataaran II Village with a sample of 97 respondents taken using the total sampling technique. Data collection was carried out using a questionnaire that had been tested for validity and reliability. The results showed that 32 people (32.99%) gave exclusive breastfeeding to their babies, meanwhile, the majority of respondents, 65 people (67.01%) did not give exclusive breastfeeding. The level of knowledge of the majority of mothers was in the sufficient category, namely 68 people (70.10%), while 26 people (26.80%) had knowledge in the good category, and only 3 people (3.09%) had insufficient knowledge. Furthermore, 87 respondents (89.69%) received good family support, while 10 respondents (10.31%) reported adequate family support, and no respondents reported inadequate family support. The bivariate analysis concluded that there was a significant relationship between maternal knowledge and exclusive breastfeeding, but no significant relationship between family support and exclusive breastfeeding.